Implementation of Tbc Management Programs at Rawa Buntu Public Health Center City of Tangerang Selatan During The Covid-19 Pandemic in 2021 - Zulva Nur Rizqy Amalia; Amira Mhuthia Adila; Zahro Mufida (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Indonesia is included in 8 countries that account for 2/3 of TB cases worldwide. Of these cases, only 67% were found and treated, so there were 283,000 patients. The COVID-19 pandemic has also exacerbated 2 determinants of TB incidence, namely decreased income and malnutrition. This research is qualitative research with the descriptive method by conducting interviews with 5 informants. The COVID-19 pandemic has brought changes to the implementation of the TB program at the Public Health Center, especially in the aspects of health promotion, surveillance, risk factor control, and case management. Health promotion is carried out online, surveillance is hampered so that it is not optimal, risk factor control is still running and case handling still requires the role of cadres.